Impoliteness Strategies on Online Comments at Kompas TV YouTube Channel: A Pragmatic Analysis - Hendar Hendar; Atri Nadia Astarina; Heri Heryono; Ida Zuraida; Meita L Sujatna (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Communicating through social media requires proper communicative strategies to avoid any social conflict and disharmony that might happen for the improper strategies applied. Those related to politeness and impoliteness in utterance turn to be generic as in speech in the YouTube comments. This research proposes an analysis of impoliteness strategies as firstly proposed by Culpeper (2005). The proposed impoliteness strategies are classified into five categories; Bald on record, Positive, Negative, Sarcasm, and Withhold Impoliteness. This research applied a descriptive qualitative method in presenting analysis based on data collected from YouTube comments sourced from KOMPAS TV. The data from 100 comments containing impoliteness strategies on that video indicated that there were four categories of impoliteness in Culpeper (2005). The four categories of impoliteness identified include: 1)bald on record; 2) positive; 3) negative; and 4) sarcasm/mock. Based on the analysis, it was revealed that the majority or 44% of comments indicated the negative impoliteness category. The positive impoliteness and bold on record were found in the same percentage, 19% throughout the comments. While the other 18% of comments showed impoliteness in the form of sarcasm/mock. The impoliteness strategies were potential to appear in a public room such as online comments as responses to controversial contents that trigger the viewers' or reader's negative attitudes. Apart from that, some factors such as age, gender, and educational background might influence the use of impoliteness strategies and can be taken as a focus in further studies.